The first Neogene record of Zygolophodon (Mammalia, Proboscidea) in Thailand: implications for the mammutid evolution and dispersal in Southeast Asia. (28th November 2016) - Duangkrayom, Jaroon; Wang, Shi-Qi; Deng, Tao; Jintasakul, Pratueng
Abstract: Lower and upper third molars of a proboscidean from the Tha Chang sand pits, Nakhon Ratchasima, northeastern Thailand, show a zygodont pattern. The crescentoids are less well developed than those of the type specimen of Zygolophodon gobiensis but similar to those of late Miocene specimens from south China assigned to Z . lufengensis and Z . chinjiensis . On the other hand, the loph(id)s are less oblique and the zygodont crests are less well developed than in Z . lufengensis and Z . chinjiensis . However, it is difficult to erect a new species for these specimens because their anterior loph(id)s are so deeply worn that the morphology of the conelets on these loph(id)s is unclear. Thus, we identify the specimens as Zygolophodon sp. Zygolophodon is known from lower and middle Miocene sediments in Africa while they are usually dated to the early–late Miocene in Europe, South Asia such as Pakistan, and Central and North China. Based on its apparent grade of dental evolution, the new material of Zygolophodon from Thailand is probably late Miocene in age. In addition, this discovery is the first record of a zygodont proboscidean in Southeast Asia.